Polyester yarn and its manufacturing method

By using harmless organic tin compound catalysts in the production of polyester yarns, environmental pollution and yarn breakage problems caused by traditional rust-resistant iridium catalysts are solved, and high-quality polyester yarn production and environmentally friendly production processes are achieved.

JP7659049B2Active Publication Date: 2025-04-08HYOSUNG TNC CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2023512234
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-17
Filing Date
2021-08-18
Publication Date
2025-04-08
Estimated Expiration
2041-08-18

AI Technical Summary

Technical Problem

The antimony catalyst used in the prior art has toxicity and environmental pollution problems in the production process of polyester yarns. At the same time, the catalyst residue causes the yarn to be easily broken during the textile process, affecting the excellent performance of the yarn.

Method used

Using harmless organotin compound catalysts, the use of organotin compounds to replace the traditional anti-rust iridium catalysts in the polyester yarn production process reduces catalyst residues and improves the stability and performance of the yarn.

Benefits of technology

The production of polyester yarn without rust-resistant iridium catalyst residues is achieved, reducing environmental pollution and human body harm, improving the stability and excellent performance of the yarn, especially in the textile process, the yarn is easily broken.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659049000001
    Figure 0007659049000001
  • Figure 0007659049000002
    Figure 0007659049000002
  • Figure 0007659049000003
    Figure 0007659049000003
Patent Text Reader

Abstract

The present invention relates to a polyester raw yarn containing a polyester obtained by polymerization in the presence of an inorganic tin compound catalyst, and a method for producing the same. The polyester raw yarn containing the inorganic tin compound of the present invention can overcome the problems caused by the residue of antimony catalyst and has excellent warping properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester raw yarn and a manufacturing method thereof, and more particularly to a polyester raw yarn having excellent warping properties while eliminating problems caused by residual antimony catalysts, and a manufacturing method thereof. [Background technology]

[0002] Polyesters, typified by polyethylene terephthalate, have excellent mechanical and chemical properties and have been widely used in a variety of fields, such as beverage containers, medical supplies, clothing, packaging materials, sheets, films, tire cords, and molded parts for automobiles.

[0003] In particular, polyester yarn is cheaper than nylon fiber, yet has high strength and various excellent properties that make it suitable for use as a clothing material, such as abrasion resistance, chemical resistance, shape stability, drapeability, washability, and sewability, and is widely used in clothing, industrial, medical, and other fields.

[0004] The most commercially successful catalysts for polyester polymerization used in the manufacture of polyester yarn are antimony-based catalysts. However, products made with antimony-based catalysts require the use of large amounts of antimony in the polymerization process, and because of the toxicity of the metal itself, if antimony is released and introduced into the body over a long period of use, it can cause diseases such as fetal growth inhibition and carcinogenicity, as well as environmental problems (Anal.Bioanal.Chem.2006,385,821).

[0005] For example, fibers made from polyester polymers produced using high concentrations of antimony catalysts may experience breakage or other defects during spinning.

[0006] In addition, when antimony catalyst is used in polyester polymerization reaction, catalyst reduction products are generated at about 10~15% of the input amount, which lowers the L value of polyester yarn color and can cause process problems such as contamination of spinnerets, increase in pressure, and yarn breakage. Patent Document 1 discloses a technique for producing polyester using titanium, a typical environmentally friendly metal, as a catalyst.

[0007] However, titanium catalysts have problems such as a large degree of yellowing of the resin, poor color tone of the resin, poor thermal stability, and high oligomer content.Due to these shortcomings, titanium catalysts are limited in that they are difficult to commercially apply to polyester production, even though the activity of the metal itself is excellent.

[0008] Meanwhile, Patent Document 2 discloses the production of polyester using a mixture of environmentally friendly metals, germanium, aluminum, and zirconium. However, although the germanium compound catalyst itself has high activity, the germanium catalyst has a limitation in that it is difficult to apply commercially if a large amount is used for polymerization due to the high price of the catalyst. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] U.S. Patent Publication No. 2010-0184916 [Patent Document 2] U.S. Patent No. 6,365,659 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made to solve the problems of the prior art as described above, and an object of the present invention is to provide a polyester fiber that does not release antimony by not using an antimony-based catalyst that is harmful to the human body and the environment.

[0011] Another object of the present invention is to provide a polyester raw yarn having excellent warping properties without using an antimony-based catalyst which causes health and environmental problems. [Means for solving the problem]

[0012] One aspect of the present invention for solving the above-mentioned technical problem is to The present invention relates to a polyester raw yarn containing a polyester obtained by polymerization in the presence of an inorganic tin compound catalyst.

[0013] The inorganic tin compound catalyst is an inorganic stannous tin compound or an inorganic stannic tin compound.

[0014] Non-limiting examples of the inorganic stannous compound are selected from the group consisting of stannous oxide, stannous pyrophosphate, stannous phosphate, stannous tartrate, stannous acetate, stannous oxalate, stannous stearate, stannous oleate, stannous gluconate, stannous citrate, stannous 2-ethylhexanoate, stannous ethoxide, stannous acetylacetonate, and stannous glycolate.

[0015] Non-limiting examples of the inorganic stannic compounds are selected from the group consisting of stannic oxide, stannic pyrophosphate, stannic phosphate, stannic tartrate, stannic acetate, stannic oxalate, stannic stearate, stannic oleate, stannic gluconate, stannic citrate, stannic 2-ethylhexanoate, stannic ethoxide, stannic acetylacetonate, and stannic glycolate.

[0016] The inorganic tin compound catalyst may be a composite of multiple types, and may be used in combination with a conventionally known catalyst.

[0017] The polyester raw yarn contains one or more of polyethylene terephthalate, polytrimethylene terephthalate, polytetramethylene terephthalate, and polybutylene terephthalate, and contains 10 ppm to 200 ppm of inorganic tin compound residues.

[0018] The polyester raw yarn is a core-sheath type composite fiber, and the polyester is disposed in the sheath of the core-sheath type composite fiber.

[0019] The polyester raw yarn of the present invention is a modified cross-section yarn or a false twisted crimp textured yarn.

[0020] Another aspect of the present invention for solving the above-mentioned technical problem is to The present invention relates to a method for producing polyester yarn, which comprises polymerizing a polymerization starting material consisting of an ester of a dicarboxylic acid component and a glycol component in the presence of an inorganic tin compound catalyst to obtain a polyester polymer, and then melt-spinning the polyester polymer to produce a polyester yarn. Effect of the Invention

[0021] According to the present invention, a catalyst that does not contain heavy metals that are harmful to humans and the environment is used, so that polyester raw yarn that does not pollute the environment and does not contain components that are harmful to the human body can be produced.

[0022] The polyester polymerization catalyst comprising the inorganic tin compound of the present invention is not only environmentally friendly but also has high catalytic activity, so that the catalyst input amount can be reduced to 1 / 5 compared to the conventional antimony catalyst, and the thermal decomposition products of polyester can be improved by 50% or more.

[0023] The polyester raw yarn of the present invention has improved processability since there is little occurrence of yarn breakage or defects during the spinning process, does not release antimony which is harmful to the human body, and can ensure excellent warping properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will now be described in more detail.

[0025] In describing the present invention, if it is determined that a detailed description of related prior art may make the gist of the present invention unclear, the detailed description will be omitted. In this specification, when a part "contains" a certain component, this does not mean that the part "contains" other components, but that the part further contains other components, unless otherwise specified.

[0026] The polyester fiber of one embodiment of the present invention is characterized in that it contains a polyester obtained by polymerization in the presence of an inorganic tin compound catalyst.

[0027] The inorganic tin compound catalyst may be used alone, or in combination of two or more kinds, or in combination with a conventionally known catalyst.

[0028] Organotin compound catalysts are excluded from the present invention because they are subject to stricter environmental regulations than the inorganic tin compounds used in the present invention.

[0029] The inorganic tin compounds used in the present invention have a significant advantage in that they have a lower standard reduction potential energy value than the conventionally used antimony (Sb) catalysts and are not easily reduced during the polyester polymerization reaction and spinning process.

[0030] The inorganic tin compound catalyst used in the present invention does not have the problem of being easily reduced during the polymerization reaction to reduce its activity or leaving catalyst residue in the polymerization reactor due to the reduction product, and it has the result of improving processability because there is little increase in filter pressure of the extruder and little generation of nozzle foreign matter during the spinning process.

[0031] TIFF0007659049000001.tif27170

[0032] The higher the standard reduction potential, the greater the reducing power, and the lower the value, the less reducing power. Antimony (Sb), which has traditionally been used primarily in polyester polymerization, has a positive (+) standard reduction potential when in the catalytically active oxidation state of 3 or 5.

[0033] In contrast, the inorganic tin compound catalyst used in the present invention is non-spontaneously reduced to the oxidation state of 2 (RPE is a negative value), so it maintains its catalytic activity and can reduce the amount of reduction products (catalyst residues) generated during the polyester polymerization and extrusion processes.

[0034] The inorganic tin compound is preferably tin oxalate, tin acetate, or tin glycolate.

[0035] The inorganic tin compound is an inorganic stannous compound or an inorganic stannic compound.

[0036] The inorganic stannous compound is selected from the group consisting of stannous oxide, stannous pyrophosphate, stannous phosphate, stannous tartrate, stannous acetate, stannous oxalate, stannous stearate, stannous oleate, stannous gluconate, stannous citrate, stannous 2-ethylhexanoate, stannous ethoxide, stannous acetylacetonate, and stannous glycolate.

[0037] The inorganic stannic compound is selected from the group consisting of stannic oxide, stannic pyrophosphate, stannic phosphate, stannic tartrate, stannic acetate, stannic oxalate, stannic stearate, stannic oleate, stannic gluconate, stannic citrate, stannic 2-ethylhexanoate, stannic ethoxide, stannic acetylacetonate, and stannic glycolate.

[0038] The inorganic tin compound catalyst of the present invention can be added at any step during polyester polymerization. For example, it can be added only during the preparation of a slurry (EG / TPA mixture) before the esterification reaction step, only during the esterification reaction step, only during the polycondensation step of the esterification reaction step, or during the preparation of a slurry before the esterification reaction step, the esterification reaction step, and the polycondensation step. However, when a polyester is prepared by polycondensing the reactants after esterification of a dicarboxylic acid component and a glycol component, the inorganic tin compound catalyst is preferably added to the polycondensation step of the esterification reactant.

[0039] The inorganic tin compound catalyst may be added to the polyester process in the form of a powder or in the form of a catalyst solution, or may be prepared in an ethylene glycol solution and then added. However, when the catalyst is prepared in an ethylene glycol solution and then added, it is preferable to react the ethylene glycol solution with the inorganic tin compound to prepare tin glycolate and then add the resulting solution.

[0040] Antimony catalysts, which are generally used as polyester polymerization catalysts, have low catalytic activity and are used in an amount of 50 ppm to 500 ppm (based on the amount of Sb element) based on polyester.

[0041] In contrast, in the case of the inorganic tin compound catalyst newly applied in the present invention, even a small amount of 10 ppm to 200 ppm, preferably 10 ppm to 100 ppm (Sn element amount) can sufficiently ensure equivalent polycondensation reactivity.

[0042] Such a low catalyst content improves the amount of catalyst foreign matter in the polyester, and the generation of foreign matter in the spinning process due to catalyst reduction products is low, resulting in an effect of improving die foreign matter.

[0043] Unlike antimony-based catalysts, the inorganic tin compound catalyst of the present invention has a relatively low toxicity of the metal itself, so it is unlikely to cause problems for people and the environment, and does not emit antimony. Polyester yarns using other non-antimony catalysts, i.e., titanium compound catalysts, do not release antimony but have the problem of poor warping properties. On the other hand, the polyester yarns of the present invention using inorganic tin compound catalysts do not release antimony and have excellent warping properties.

[0044] The polyester polymers used in the present invention contain a minimum of 85% ethylene terephthalate units, and preferably consist exclusively of ethylene terephthalate units. Optionally, the polyesters incorporate as copolymer units minor amounts of units derived from one or more ester forming components other than ethylene glycol and aromatic dicarboxylic acids, or derivatives thereof.

[0045] Examples of other ester-forming components copolymerizable with ethylene terephthalate units include glycols such as 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, and the like, and dicarboxylic acids such as terephthalic acid, isophthalic acid, hexahydroterephthalic acid, stilbene dicarboxylic acid, bibenzoic acid, adipic acid, sebacic acid, and azelaic acid.

[0046] In the polyester raw yarn, the cross-sectional shape of the staple fiber is not particularly limited. In addition, such polyester raw yarn may be subjected to normal air processing, false twist crimp processing, and twisting. The polyester raw yarn according to the present invention preferably has a strength of 3.0 g / d or more. If it is less than 3.0 g / d, the strength is reduced, and the tear strength is reduced when the raw yarn is manufactured into a roll, which is not preferable.

[0047] The polyester raw yarn of the present invention is processed into fabrics such as woven fabrics, knitted fabrics, and nonwoven fabrics. For example, examples of weaves of fabrics include ternary weaves such as plain weave, twill weave, and satin weave, altered weaves such as altered weave and altered twill weave, plain double weaves such as warp double weave and weft double weave, warp pile weaves such as warp velvet, towel, and velour, and weft pile weaves such as cotton velvet, weft velvet, velvet, and corduroy. Fabrics having these weaves are woven by ordinary methods using ordinary weaving machines such as rapier looms and air jet looms.

[0048] The number of layers is not particularly limited, and may be a single layer or a woven fabric having a multi-layer structure of two or more layers.

[0049] The type of knitted fabric may be either a weft knitted fabric or a warp knitted fabric. Preferred weft knitted structures include plain knitted fabric, rib knitted fabric, double knitted fabric, purl knitted fabric, tuck knitted fabric, float stitch knitted fabric, half cardigan knitted fabric, lace knitted fabric, and plating knitted fabric. Preferred warp knitted structures include single denbigh knitted fabric, single atlas knitted fabric, double cord knitted fabric, half tricot knitted fabric, fleecy knitted fabric, and jacquard knitted fabric.

[0050] The knitting is carried out by a conventional method using a conventional knitting machine such as a circular knitting machine, a flat knitting machine, a tricot knitting machine, a raschel knitting machine, etc. The number of layers is not particularly limited, and the knitted fabric may be a single layer or may have a multi-layer structure of two or more layers.

[0051] Next, the textile product of the present invention is made using the above-mentioned fabric, and is any one textile product selected from the group consisting of sportswear, outdoor wear, raincoats, umbrellas, men's clothing, women's clothing, work clothes, protective clothing, artificial leather, shoes, bags, curtains, waterproof sheets, tents, and car seats.

[0052] Another aspect of the present invention relates to a method for producing polyester yarn, in which a starting material for polymerization, which is an ester of a dicarboxylic acid component and a glycol component, is polymerized in the presence of an inorganic tin compound catalyst to obtain a polyester polymer, which is then melt-spun to produce a polyester yarn.

[0053] In producing the polyester polymer, a dicarboxylic acid component and a glycol component are polymerized in the presence of a catalyst composition containing an inorganic tin compound.

[0054] The step of polymerizing the dicarboxylic acid component and the glycol component includes a step of esterifying the dicarboxylic acid component and the glycol component, and a step of polycondensing the reaction product of the esterification reaction. In the esterification reaction step, a low polymer is obtained by transesterification, and then organic polymer particles and various additives are added, and an inorganic tin compound is added as a polycondensation catalyst to carry out a polycondensation reaction to obtain a high molecular weight polyester.

[0055] More specifically, the dicarboxylic acid component and the glycol component are first subjected to an ester reaction. According to an embodiment of the present invention, the dicarboxylic acid component may be, for example, terephthalic acid, oxalic acid, malonic acid, azelaic acid, fumaric acid, pimelic acid, suberic acid, isophthalic acid, dodecanedicarboxylic acid, naphthalenedicarboxylic acid, biphenyldicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, 2,6-naphthalenedicarboxylic acid, 1,2-norbornanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,4-cyclobutanedicarboxylic acid, 5-sodium sulfoisophthalic acid, 5-potassium sulfoisophthalic acid, 5-lithium sulfoisophthalic acid, or 2-sodium sulfoterephthalic acid, but is not limited thereto.

[0056] In addition to the above-mentioned dicarboxylic acids, other dicarboxylic acids not exemplified above may be used within the scope of not impairing the object of the present invention.

[0057] According to one embodiment of the present invention, terephthalic acid is used as the dicarboxylic acid component. According to an embodiment of the present invention, examples of the glycol component include ethylene glycol, 1,2-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1.5-pentanediol, neopentyl glycol, 1,3-propylene glycol, diethylene glycol, triethylene glycol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, propanediol, 1,6-hexanediol, neopentyl glycol, tetramethylcyclobutanediol, 1,4-cyclohexanediethanol, 1,10-decamethylene glycol, 1,12-dodecanediol, polyoxyethylene glycol, polyoxymethylene glycol, polyoxytetramethylene glycol, and glycerol, but are not limited thereto, and other glycols may be used as long as they do not impair the object of the present invention.

[0058] Preferably, ethylene glycol is used as the glycol component.

[0059] According to one embodiment of the present invention, the step of esterifying the dicarboxylic acid component and the glycol component is carried out at a temperature of about 200° C. to about 300° C., preferably about 230° C. to about 280° C., for about 1 to 6.5 hours, preferably about 2 to 5 hours.

[0060] Next, the esterification reaction product is polycondensed. The step of polycondensing the esterification reaction product is carried out at a temperature of about 200° C. to about 300° C., preferably about 260° C. to about 290° C., under reduced pressure of about 0.1 to about 1 torr, for about 1 to about 3 hours, preferably about 1 hour 30 minutes to 2 hours 30 minutes.

[0061] The inorganic tin compound catalyst of the present invention is introduced during the preparation of the slurry prior to the esterification reaction or during the esterification reaction and prior to the polycondensation step after the esterification reaction.

[0062] However, although the inorganic tin compound catalyst of the present invention is effective in improving the esterification reaction, it has little effect in improving the polycondensation time and there is a concern that the content of diethylene glycol (DEG), a by-product of the esterification reaction, increases slightly, so in the present invention, it is preferable to add the reactant after the esterification reaction to the polycondensation step. By doing so, the polycondensation time can be significantly shortened and productivity can be increased compared to when using conventional catalysts.

[0063] In the method for producing polyester fiber of the present invention, the inorganic tin compound catalyst is used in an amount of about 200 ppm or less, for example, about 10 to about 200 ppm, preferably about 10 to 100 ppm, based on the content of tin element contained in the inorganic tin compound catalyst relative to the mass of the finally produced polyester.

[0064] In the present invention, if the amount of inorganic tin compound catalyst is less than 10 ppm, the polymerization reaction rate will be slow, resulting in a polymer with low viscosity, which will result in poor physical properties during yarn production, poor spinning workability, and low productivity.If the amount of inorganic tin compound catalyst is more than 200 ppm, the inorganic tin compound in excess of the required amount will act as a foreign matter, which may reduce the workability of spinning and drawing, and the warping property will be poor.

[0065] According to the present invention, the use of an inorganic tin compound allows the polymerization reaction to be carried out using a small amount of catalyst. Also, a product with high viscosity can be obtained in a short reaction time. As a result, the amount of catalyst used can be reduced, which reduces the greyish phenomenon of the polyester polymer generated after polymerization and increases the viscosity of the conventional low polymer, which is very advantageous commercially.

[0066] According to the method for producing polyester fiber of the present invention, the polyester is formed by liquid polymerization, and the polyester thus formed has an intrinsic viscosity in the range of about 0.50 to 0.75 dl / g.

[0067] If the intrinsic viscosity of the polyester is less than 0.50 dl / g, the tensile strength of the polyester yarn may be reduced, whereas if the intrinsic viscosity of the polyester is more than 0.75 dl / g, the productivity of the polyester yarn may be reduced.

[0068] As a method for spinning polyester polymer, fibers are produced by a normal melt spinning method, and a method in which spinning and drawing are carried out in two steps and a method in which spinning and drawing are carried out in one step are adopted.

[0069] In the spinning process, polyester chips are melted at a temperature of 280~320℃, extruded, spun, and then rapidly cooled to solidify. Depending on the method of blowing cooling air in the cooling step, open quenching method, circular closed quenching method, spinning type outflow quenching method, spinning type inflow quenching method, etc. are applied.

[0070] Generally, the temperature of the cooling air is adjusted to 20 to 50 degrees Celsius. The released yarn that has been cooled and solidified is oiled by an oil application device.

[0071] The present invention will be described in more detail with reference to the following examples, however, these examples are merely presented as examples of the invention and do not limit the scope of the invention.

[0072] Working Example Example 1 Preparation of catalyst solution 5 g of the inorganic tin compound catalyst shown in Table 1 below was diluted with ethylene glycol to a total mass of 2 kg, and the mixture was stirred at a stirring speed of 400 rpm to prepare an inorganic tin compound catalyst at a concentration of 0.25% in ethylene glycol. Next, the mixture was reacted in a reactor capable of refluxing at a reaction temperature of 160 to 180°C for 2 hours to produce an inorganic tin compound catalyst.

[0073] Polyester chip manufacturing A slurry was prepared from 7.8 kg of terephthalic acid (TPA) and 3.3 kg of ethylene glycol (EG) (EG / TPA molar ratio = 1.13), which was then charged into an esterification reactor in a semi-batch manner and reacted at atmospheric pressure in a nitrogen atmosphere until the reaction temperature reached 265°C to produce a polyester oligomer.

[0074] The esterification reaction temperature was 235℃ when the slurry was introduced and 265℃ at the end of the final esterification reaction, with the reaction time being approximately 3 hours and 30 minutes. The PET oligomer produced in the esterification reactor was transferred to the polycondensation reactor, where 200ppm of tin oxide catalyst was added based on the final PET, and polycondensation was carried out for approximately 2 hours and 30 minutes under high vacuum and reduced pressure until the reaction temperature reached 288℃. After the polycondensation reaction was completed, the mixture was solidified using cooling water, and a polyethylene terephthalate polymer with an intrinsic viscosity (IV) of 0.60~0.65dl / g was obtained.

[0075] Manufacture of polyester yarn The produced chips were melt-spun at 290°C using an extruder, and the discharged yarn was then passed through a 60mm long heating zone (ambient temperature 340°C) directly below the nozzle and a 500mm long cooling zone (cooling air was blown in at 20°C and a wind speed of 0.5m / sec) to solidify, and then oiled with a spinning oil (containing 70% paraffin oil). This was wound up at a spinning speed of 4,500m / min and a draw ratio of 2.25 to produce a final polyester yarn of 50d / 24f.

[0076] Examples 2 to 100 Polyester yarn was produced in the same manner as in Example 1, except that polyester chips produced using 10 to 200 ppm of an inorganic tin compound shown in Tables 1 to 5 below as a catalyst were used.

[0077] Comparative Example 1 Polyester yarn was produced in the same manner as in Example 1, except that no catalyst was used.

[0078] Comparative Example 2 40 g of antimony compound was dissolved in ethylene glycol to a total weight of 2 kg, and the solution was stirred at 400 rpm to prepare a catalyst solution. The mixture was reacted in a refluxable reactor at a reaction temperature of 180-190°C for 2 hours to prepare an antimony glycolate solution. Polyester yarn was produced in the same manner as in Example 1, except that polyester polymerized using the obtained antimony compound catalyst solution was used.

[0079] Comparative Examples 3 to 9 Polyester yarn was produced in the same manner as in Example 1, except that a polyester polymer prepared using an antimony catalyst shown in Table 1 below was used as a catalyst.

[0080] Comparative Example 10 40g of titanium compound was dissolved in ethylene glycol to a total weight of 2kg, and stirred at 400rpm to prepare a catalyst solution. The mixture was reacted in a refluxable reactor at a reaction temperature of 180~190℃ for 2 hours to prepare a titanium glycolate solution. Polyester yarn was produced in the same manner as in Example 1, except that polyester polymerized using the obtained titanium catalyst solution was used.

[0081] Comparative Examples 11 to 17 Polyester yarn was produced in the same manner as in Example 1, except that the polyester polymer was prepared using the titanium compound catalyst shown in Table 1 below as the catalyst.

[0082] Comparative Examples 18 to 77 Polyester yarn was produced in the same manner as in Example 1, except that polyester polymers prepared using 1 ppm, 8 ppm, or 500 ppm of inorganic tin compounds shown in Tables 1 to 5 below as catalysts were used.

[0083] Test Example The physical properties of the polyester yarns produced in Examples 1 to 100 and Comparative Examples 1 to 77 were evaluated by the following methods, and the results are shown in Tables 1 to 5 below.

[0084] (1) Method for measuring strength and elongation of raw yarn The raw yarn is left under standard conditions, i.e., in a temperature and humidity chamber at 25°C and 65% relative humidity, for 24 hours, and then the sample is measured using a tensile tester according to the ASTM 2256 method.

[0085] (2) Number of thread cuts during spinning The number of thread breaks during 24-hour spinning on an 8-pos. spinning machine is recorded. Number of thread trimmings (ea / pos. / day) = Number of thread trimmings / 8pos. x 24 hours / production time

[0086] (3) Warping ability The number of interruptions to the warping process (interruptions due to thread breaks are detected by a sensor) is recorded when the raw yarn is put into the warper and displayed as the number of interruptions per 10 million meters. Warping performance differs depending on the user, but generally, 0.5 ea / 10 million meters or more is considered defective, and 1.0 ea / 10 million meters or more is not suitable for use as raw cloth.

[0087] (4) Amount of antimony eluted The amount of antimony leached is determined according to the method DIN EN 16711-2 (2016).

[0088] [Table 1]

[0089] [Table 2]

[0090] [Table 3]

[0091] [Table 4]

[0092] [Table 5]

[0093] Referring to Tables 1 to 5, it was confirmed that in Examples 1 to 100, the physical properties of the polyethylene terephthalate yarn produced were equal to or better than those of Comparative Examples 2 to 9 in which an antimony catalyst was used, and no antimony elution occurred. Also, in Comparative Examples 10 to 17 in which a titanium compound was used, antimony was not eluted, but the warping properties were high and the yarn was suitable for use as a raw yarn. [Industrial Applicability]

[0094] According to the present invention, a polyester raw yarn having excellent manufacturing processability is provided. The polyester raw yarn has excellent warping properties because it hardly generates fluff, and enables the production of very high quality raw yarn for clothing from which antimony is not eluted. The polyester raw yarn of the present invention is advantageously used as a textile material for high quality clothing and interiors.

[0095] Although the present invention has been described above using limited examples, the present invention is not limited thereto, and it is of course possible for a person having ordinary skill in the art to which the present invention pertains to make various modifications and variations of the technical concept of the present invention.

[0096] Therefore, the true scope of protection of the present invention should be determined by the following claims and their equivalents.

Claims

1. A polyester yarn containing 10 to 200 ppm of an inorganic stannous compound as a polymerization catalyst and containing no catalyst other than the inorganic stannous compound, The inorganic stannous compound is selected from the group consisting of stannous pyrophosphate, stannous phosphate, stannous tartrate, stannous oxalate, stannous stearate, stannous oleate, stannous citrate, stannous ethoxide, stannous acetylacetonate, and stannous glycolate.

2. The polyester polymer is selected from one or more of polyethylene terephthalate, polytrimethylene terephthalate, polytetramethylene terephthalate, and polybutylene terephthalate. The polyester fiber according to claim 1.

3. The polyester yarn is a core-sheath type composite fiber, and the polyester is disposed in the sheath of the core-sheath type composite fiber. The polyester fiber according to claim 1.

4. The polyester raw yarn is a modified cross-section yarn. The polyester fiber according to claim 1.

5. The polyester raw yarn is a false twisted crimped yarn. The polyester fiber according to claim 1.

6. A method for producing polyester yarn, comprising: polymerizing a polymerization starting material consisting of an ester of a dicarboxylic acid component and a glycol component in the presence of an inorganic tin compound catalyst alone to obtain a polyester polymer; and melt-spinning the polyester polymer to produce a polyester yarn, the method comprising: Add 10 ppm to 200 ppm of an inorganic stannous compound based on the content of tin contained in the inorganic tin compound catalyst to a sample of polyester to be finally produced; The inorganic stannous compound catalyst is prepared in an ethylene glycol solution and added; A method for producing polyester yarn, wherein the inorganic stannous compound catalyst is selected from the group consisting of stannous pyrophosphate, stannous phosphate, stannous tartrate, stannous oxalate, stannous stearate, stannous oleate, stannous citrate, stannous ethoxide, stannous acetylacetonate, and stannous glycolate.

7. The inorganic tin compound catalyst is added during the preparation of a slurry before the esterification reaction, during the esterification reaction, or during the polycondensation step after the esterification reaction; The method for producing the polyester fiber according to claim 6.

8. The method includes adding a polyester polymerization catalyst containing an inorganic tin compound to a polyester process in powder form or in the form of a catalyst solution; The method for producing the polyester fiber according to claim 6.

Citation Information

Patent Citations

  • Facsimile controller

    JP1984045763A

  • Production of polybutylene terephthalate of low terminal-carboxyl group content

    JP1984086622A

  • Electromagnetic wave shielding conjugated yarn

    JP1987057919A

  • Polyether ester-based elastic fiber

    JP1992300323A

  • Conjugate polyester fiber

    JP1996092818A